Expolarisation Figures and Attachment Forms in Twins - Novia Wati, Risa; Asih Fitriani; Annisa Ayu Kusumaningrum (Universitas Muhammadiyah Yogyakarta, 2025)
The figures and forms of attachment experienced by twins are very important and should be explored in the field of development. This can serve to broaden the horizons of parents, educators and professionals. This study used a qualitative approach. The subjects in this study were 3 pairs of twins and 3 parents. The purpose of this study was to describe the dominant attachment figure in twins, to find out the forms of attachment of twins and to find out the factors that influence the occurrence of twin attachment. The results of this study are that there are two dominant attachment figures in twins, namely parents (mothers) and children, the form of attachment in twins consists of two kinds, namely safe and avoidant attachment and factors that influence attachment are two, namely parental treatment and individual personality.